Production of melatonin and other tryptophan derivatives by Oenococcus oeni under winery and laboratory scale. (April 2020) - Fracassetti, Daniela; Francesco Lo Faro, Alfredo Fabrizio; Moiola, Sonia; Orioli, Marica; Tirelli, Antonio; Iriti, Marcello; Vigentini, Ileana; Foschino, Roberto
Abstract: Malolactic fermentation (MLF) in Valtellina Superiore DOCG red wine was monitored in 4 cellars and the final products were analysed to determine the content of melatonin (MEL) and other tryptophan (TRP) derivatives, including tryptophan ethyl ester (TEE) and MEL isomers (MISs), and to isolate predominant O. oeni strains. MEL and TEE significantly increased in wines after MLF from two cellars out of four. Six strains were isolated during the MLF of red wines and under laboratory scale, in rich and synthetic wine cultural media, together with other four O. oeni strains able to trigger the MLF. Results showed that the presence of stressful growth factors, like ethanol and acid pH, has a pivotal role in triggering the release of TEE by oenococci. Indeed, all the strains became capable to produce also MEL and MISs, together with TEE. under harsh growth conditions, as in a synthetic wine medium. The production of these compounds was strain-dependent and a maximum amount of 0.0078 ± 0.0023 ngT /mL (UMB472) and 619.85 ± 196.16 ngT /mL (UMB436) of MEL and TEE was obtained, respectively. In particular, different MISs were detected under oenological and laboratory scale suggesting that other factors (i.e. technological and/or physico-chemical) could affect the synthesis of TRP derivatives. Highlights: Tryptophan derivatives were detected during the malolactic fermentation. Release of tryptophan derivatives by Oenococcus oeni strains was investigated. Stress factors (ethanol and acid pH) trigger the production of tryptophan derivatives by O. oeni. O. oeni produced melatonin and tryptophan derivatives in synthetic wine medium. Oenococci-mediated release of tryptophan derivatives resulted strain-dependent.